A review on the synergism between corrosion and fatigue of magnesium alloys: Mechanisms and processes on the micro-scale - Mara Cristina Lopes de Oliveira; Rejane Maria Pereira da Silva; Ricardo M. Souto; Renato Altobelli Antunes (Journal of Magnesium and Alloys)
Understanding the interaction between cyclic stresses and corrosion of magnesium (Mg) and its alloys is increasingly in demand due to the continuous expansion of structural applications of these materials. This review is dedicated to exploring the corrosion-fatigue mechanisms of these materials, with an emphasis on microscale processes, and the possibility of expanding current knowledge on this topic using scanning electrochemical techniques. The interaction between fatigue and corrosion of Mg alloys is analyzed by considering the microstructural aspects (grain size, precipitates, deformation twins), as well as the formation of pits. Furthermore, in the case of coated alloys, the role of coating defects in these phenomena is also described. In this context, the feasibility of using scanning electrochemical microscopy (SECM), scanning vibrating electrode technique (SVET), scanning ion-selective electrode technique (SIET), localized electrochemical impedance spectroscopy (LEIS) and scanning Kelvin probe (SKP) methods to study the corrosion-fatigue interaction of Mg alloys is examined. A comprehensive review of the current literature in this field is presented, and the opportunities and limitations of consolidating the use of these techniques to study the microscale processes involved in Mg corrosion-fatigue are discussed.